Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4103/0976-237x.111588
|View full text |Cite
|
Sign up to set email alerts
|

Shear bond strength and SEM morphology evaluation of different dental adhesives to enamel prepared with ER:YAG laser

Abstract: Context:Early observations of enamel surfaces prepared by erbium lasers motivated clinicians to use laser as an alternative to chemical etching.Aims:Evaluate shear bond strength (SBS) values of different dental adhesives on Erbium:Yttrium Aluminum Garnet (Er:YAG) laser prepared enamel and to evaluate possible etching patterns correlations between dental adhesives and SBS values.Subjects and Methods:One hundred bovine incisors were randomly assigned to SBS tests on enamel (n = 15) and to enamel morphology analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 44 publications
(53 reference statements)
2
22
0
Order By: Relevance
“…Yet, results showed that the absence of smear layer formation during dentin preparation by Er:YAG laser did not improve the adhesion values of self-etching adhesive systems [22, 23]. Nevertheless, Yazici et al have proven that dentin prepared with Er:YAG laser might improve bonding effectiveness to dentin [10, 19, 24, 25], similar to using phosphoric acid prior to applying SACs [2527]. However, some other studies have reported opposite results; studies showed that laser irradiation weakens the bond strength of the adhesive [28] and that conventional etching with 35% phosphoric acid yielded significantly higher bond strength values compared to thermal etching with the Er:YAG laser [29].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, results showed that the absence of smear layer formation during dentin preparation by Er:YAG laser did not improve the adhesion values of self-etching adhesive systems [22, 23]. Nevertheless, Yazici et al have proven that dentin prepared with Er:YAG laser might improve bonding effectiveness to dentin [10, 19, 24, 25], similar to using phosphoric acid prior to applying SACs [2527]. However, some other studies have reported opposite results; studies showed that laser irradiation weakens the bond strength of the adhesive [28] and that conventional etching with 35% phosphoric acid yielded significantly higher bond strength values compared to thermal etching with the Er:YAG laser [29].…”
Section: Introductionmentioning
confidence: 99%
“…7 Er,Cr:YSGG lasers are group of Erbium laser systems, that operates at a wavelength of 2.780 µm. 8 Erbium lasers produced similar surface to that of conventional phosphoric acid etching. 9 Erbium lasers with appropriate parameters selectively removes hydroxyapatite crystals from enamel producing surface irregularities that could enhance the micromechanical retention.…”
Section: Introductionmentioning
confidence: 82%
“…28 Ability of hard tissue removal without smear layer production has brought lasers into modern dentistry replacing these conventional burs. 8,29 Among various lasers, Erbium lasers (high-intensity lasers) are the most efficient and safest system of lasers, showing similarities to acid-etched enamel. 8,29 Er:Cr:YSGG lasers cut dental hard tissue with the help of its laser-powered hydrokinetic system at infrared wavelength of 2.7 to 3 µm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When a coronary lesion is restored, one of the working principles to take into account is to use materials adhering to the dental surfaces. This avoids the phenomenon of marginal infiltration (percolation), as well as the onset of dentinal hypersensitivity or postoperative pain [3]. For this reason, in restorative dentistr y practice, the mere juxtaposition of a filling material in a cavity is no longer accepted.…”
mentioning
confidence: 99%